2005
DOI: 10.1124/mol.104.009852
|View full text |Cite
|
Sign up to set email alerts
|

TRPV1b, a Functional Human Vanilloid Receptor Splice Variant

Abstract: Transient receptor potential (TRP) genes encode a family of related ion-channel subunits. This family consists of cationselective, calcium-permeable channels that include a group of vanilloid receptor channels (TRPV) implicated in pain and inflammation. These channels are activated by diverse stimuli, including capsaicin, lipids, membrane deformation, heat, and protons. Six members of the TRPV family have been identified that differ predominantly in their activation properties. However, in neurons, TRPV channe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
66
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(69 citation statements)
references
References 42 publications
3
66
0
Order By: Relevance
“…Thus, the MPD of the N terminus emerged as the only component capable of perturbing the enthalpy of the channel. It is interesting that the region maps to the missing segment in the nonfunctional TRPV1b splice variant (21,27). The effectiveness of the region throughout different channels suggests that its function is conserved.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the MPD of the N terminus emerged as the only component capable of perturbing the enthalpy of the channel. It is interesting that the region maps to the missing segment in the nonfunctional TRPV1b splice variant (21,27). The effectiveness of the region throughout different channels suggests that its function is conserved.…”
Section: Discussionmentioning
confidence: 99%
“…Another possibility is that TRPV1 triggers LTD via a nonconducting function (Kaczmarek, 2006) or via a capsaicin-resistant TRPV1. For example, the alternatively spliced variant TRPV1b has been described as a functional ion channel although it does not respond to capsaicin (Lu et al, 2005). Indeed, the authors reported TRPV1 expression [Cavanaugh et al (2011), their Fig.…”
Section: Review Of Cavanaugh Et Almentioning
confidence: 99%
“…Comparing the amplitude of the camphor response relative to the capsaicin response in each individual neuron, camphor current was between 5.8 and 71% (ϩ80 mV) of the 1 M capsaicin current. The lone camphor-responsive neuron that lacked capsaicinactivated current might have been the result of camphormediated desensitization of TRPV1 or may have expressed capsaicin-insensitive TRPV1 splice variants (Lu et al, 2005) or alternatively the presence of TRPV3 channels.…”
Section: Camphor Activation Of Trpv1-like Currents In Drg Sensory Neumentioning
confidence: 99%